Scholarship and Language Revival: Language Ideologies in Corpus Development for Revived Manx - Lewin, Christopher (Studia Celtica Posnaniensia, 2017)
In this article the role of different ideological viewpoints concerning corpus development within the Manx revival movement in the second half of the twentieth century is explored. In particular, the work of two prominent figures is examined: the Celtic scholar Robert L. Thomson, who published extensively especially on Manx language and literature, and also contributed to the revival, particularly as editor of several pedagogical resources and as a member of the translation committee Coonceil ny Gaelgey, and Douglas Fargher, a tireless activist and compiler of an English-Manx Dictionary (1979). Broadly speaking, Thomson was of a more preservationist bent, cautious in adapting the native resources of the language and wary of straying too far from attested usage of the traditional language, while Fargher was more radical and open especially to borrowing from Irish and Scottish sources. Both were concerned, in somewhat different ways, to remove perceived impurities or corruptions from the language, and were influenced by the assumptions of existing scholarship. A close reading of the work of these scholar-activists sheds light on the tensions within the revival movement regarding its response to the trauma of language death and the questions of legitimacy and authenticity in the revived variety. Particular space is devoted to an analysis of the preface of Fargher’s dictionary, as well as certain features of the body of the work itself, since this volume is probably the most widely consulted guide to the use of the language today. Finally, it is argued that the Manx language movement today would benefit from a reassessment and discussion of the ideological currents of the past and present, and a judicious evaluation of both the strengths and weaknesses of existing reference works.